32 Transradial Catheterisation: A Clinical Translational Model of Human Arterial Injury in vivo. (3rd June 2016) - Mitchell, Andrew; Fujisawa, Takeshi; Mills, Nicholas; Newby, David; Cruden, Nicholas
Abstract : Introduction: Endothelial outgrowth cells (EOC) isolated from the circulation can be expanded in culture and have major potential as a therapy for vascular regeneration, but investigation of their role in vascular repair has been limited by the lack of a safe model of arterial injury in man. We developed a GMP-compliant culture process for EOC production and characterised the functional response to vascular injury in patients undergoing transradial cardiac catheterization. Methods: Patients with stable angina (n = 50, 63.8 ± 10.8 years) undergoing transradial cardiac catheterization had an assessment of flow-mediated dilatation (FMD) in both radial arteries prior to catheterisation and at 24 h, 1, 4 and 12 weeks. Peripheral blood was obtained for the isolation and quantification of EOC, and for the development of a GMP-complaint protocol. Results: FMD was attenuated in the catheterised artery compared to the non-catheterised artery at 24 h (4.3 ± 3.4 vs. 10.7 ± 5.6, P < 0.05) and at one week (3.1 ± 4.1 vs. 7.7 ± 5.6, P < 0.05), but had recovered by 12 weeks. EOCs were obtained in 66.67% of patients (14/21) and using a GMP-compliant protocol we were able to produce 32.1 ± 11.2 × 10 6 cells over four weeks. Conclusions: Transradial catheterization is associated with endothelial denudation and radial artery vasomotor dysfunction, and represents an accessible and reproducible model of vascular injury in man. The development of an efficient GMP-compliant culture protocol for the manufacture of EOC will permit first-in-man clinical trials to assess whether EOCs are able to home to and incorporate at sites of vascular injury in man.